2014
DOI: 10.1016/j.nlm.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise reduces diet-induced cognitive decline and increases hippocampal brain-derived neurotrophic factor in CA3 neurons

Abstract: Background Previous studies have shown that a western diet impairs, whereas physical exercise enhances hippocampus-dependent learning and memory. Both diet and exercise influence expression of hippocampal brain-derived neurotrophic factor (BDNF), which is associated with improved cognition. We hypothesized that exercise reverses diet-induced cognitive decline while increasing hippocampal BDNF. Methods To test the effects of exercise on hippocampal-dependent memory, we compared cognitive scores of Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 84 publications
(113 reference statements)
3
57
2
1
Order By: Relevance
“…A positive correlation between CA3 TrkB expression and percent time spent with the novel object suggests that CA3 TrkB may be one of the neuronal factors for BEP specific contextual learning deficit. Previous studies employing unrestricted HFD-fed rodents have found that spatial learning and memory impairments are associated with decreased hippocampal Bdnf expression [41, 42, 74, 75], which differs from the increased CA3 Bdnf expression and learning impairments found in the BEP rats in our study. The increased Bdnf expression may be a consequence of the downregulated TrkB expression in the CA3 region, or vice versa, which in part is supported by one study showing the contrasting regulation of Bdnf and its receptor, TrkB in the primary neuronal cultures [76].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…A positive correlation between CA3 TrkB expression and percent time spent with the novel object suggests that CA3 TrkB may be one of the neuronal factors for BEP specific contextual learning deficit. Previous studies employing unrestricted HFD-fed rodents have found that spatial learning and memory impairments are associated with decreased hippocampal Bdnf expression [41, 42, 74, 75], which differs from the increased CA3 Bdnf expression and learning impairments found in the BEP rats in our study. The increased Bdnf expression may be a consequence of the downregulated TrkB expression in the CA3 region, or vice versa, which in part is supported by one study showing the contrasting regulation of Bdnf and its receptor, TrkB in the primary neuronal cultures [76].…”
Section: Discussioncontrasting
confidence: 85%
“…Similar to the hippocampus, intact BDNF-TrkB expression in the prefrontal cortex (PFC) can regulate working memory, discrimination reversal learning as well as object recognition learning [3640]. Furthermore, effects of high fat diet on disrupting both hippocampal and cortical bdnf and trkb expression has been reported in rodent models [38, 4042]. Hippocampus and PFC interact to synchronize contextual, spatial learning and memory retrieval with working memory, decision-making, and executive functions [43, 44].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BDNF promotes the differentiation of neural stem cells into neurons, and the survival, growth and synapse formation of the newly generated neurons (Marosi and Mattson, 2014). Such effects of BDNF signaling likely play important roles in the processes by which exercise and intermittent fasting enhance cognitive function (Mattson, 2012; Noble et al, 2014). Interestingly, recent findings suggest that BDNF signaling in the brainstem enhances activation of cardiovagal (cholinergic) neurons resulting in a reduction in resting heart rate (Wan et al, 2014).…”
Section: Signaling Pathways and Molecular Mechanismsmentioning
confidence: 99%
“…Similarly, the pro-cognitive effects of the incretin analogs may result at least in part from the ability of these compounds to cross the BBB and activate hippocampal incretin signaling to promote cognition in patients with metabolic disorders [78;79]. Increased physical activity [57;80;81] and weight loss approaches [82-84] also restore behavioral performance in rodent models of T2DM and obesity, thereby supporting data indicating that lifestyle interventions enhance cognitive performance in patients with metabolic disorders. This includes aerobic exercise [85;86] and weight loss achieved through bariatric surgical procedures [87•].…”
Section: Conclusion and Translational Perspectivesmentioning
confidence: 99%